The Governance of Health Systems; Comment on "A Network Based Theory of Health Systems and Cycles of Well-Being" - Karl Blanchet (Kerman University of Medical Sciences, 2013)
Health systems research aims to understand the governance of health systems (i.e. how health systems function and perform and how their actors interact with each other). This can be achieved by applying innovative methodologies and concepts that are going to capture the complexity and dynamics of health systems when they are affected by shocks. The capacity of health systems to adapt to shocks (i.e. the resilience of health systems) is a new area of investigation. Social network analysis is a great avenue that can help measure the properties of systems and analyse the relationships between its actors and between the structure of a health system and the performance of a health system. A new conceptual framework is presented to define the governance of health systems using a resilience perspective.